2009
DOI: 10.1007/s00267-009-9392-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Information on the Social Acceptability of Alternatives to Clearfelling in Australian Wet Eucalypt Forests

Abstract: The effects of viewing different types of information were investigated in people judging the social acceptability of alternative forest harvest systems. Approximately 500 Tasmanians were shown still-simulated images of four harvest systems (a clearfell system, two aggregated retention systems, and a selective system) and were asked to judge their acceptability. Individual interviews were conducted with 12 of the participants. It was anticipated that people holding different beliefs about the consequences of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…Siegrist and Cvetkovich (2000) argue that trust in authorities has greater influence on acceptance when an individual lacks knowledge about a potential hazard, but other studies have shown that knowledge, while sometimes influential, may be less important than more subjective or emotional responses (Brunson and Shindler 2004). The latter study found no relationship between acceptability judgments for fuels reduction and general environmental concern, but other researchers have found such a relationship when measuring acceptability of timber harvest practices (Ribe 2002;Ford et al 2009). Beliefs about natural resource management often differ between urban and rural residents (e.g., Kleiven et al 2004;Racevskis and Lupi 2006); we have seen such differences in our survey as well (Shindler et al 2011).…”
Section: Introductioncontrasting
confidence: 45%
“…Siegrist and Cvetkovich (2000) argue that trust in authorities has greater influence on acceptance when an individual lacks knowledge about a potential hazard, but other studies have shown that knowledge, while sometimes influential, may be less important than more subjective or emotional responses (Brunson and Shindler 2004). The latter study found no relationship between acceptability judgments for fuels reduction and general environmental concern, but other researchers have found such a relationship when measuring acceptability of timber harvest practices (Ribe 2002;Ford et al 2009). Beliefs about natural resource management often differ between urban and rural residents (e.g., Kleiven et al 2004;Racevskis and Lupi 2006); we have seen such differences in our survey as well (Shindler et al 2011).…”
Section: Introductioncontrasting
confidence: 45%
“…Instead, individuals tend to test new information against a framework of their own existing knowledge, values and beliefs [30]. Individuals then accept, reject or adapt the new information and/or their views [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, they also found that information increased public tolerance and understanding of fire; a finding supported by Kakoyannis et al (2001). Ford et al (2009b) found that information about the consequences of forest management activities changed the relative acceptability of alternative harvesting treatments. Knowledge can also influence environmental activism, and as concluded by McFarlane and Hunt (2006: 283) "managers may be surprised that individuals with more factual knowledge of forests engage more often in environmental activism".…”
Section: Education and Informationmentioning
confidence: 76%